2010
DOI: 10.1111/j.1442-2042.2010.02603.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse expression of estrogen receptor‐β and nuclear factor‐κB in urinary bladder carcinogenesis

Abstract: Objectives:To investigate the expression of nuclear factor-kB (NF-kB) and estrogen receptor-b (ER-b) signalling pathways in bladder urothelial carcinoma according to clinicopathological features, in order to elucidate their role during carcinogenesis. Methods: Immunohistochemical methodology was carried out on formalin-fixed , paraffin-embedded sections from urinary bladder carcinomas of 140 patients (94 males and 46 females) who underwent transurethral resection of bladder neoplasms. Correlations between ER-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 54 publications
(98 reference statements)
4
44
1
Order By: Relevance
“…Shyr et al 11 showed that 36 (43%) of 83 UUTUCs, including 44% of low-grade vs. 43% of high-grade tumors (P D 1.000) as well as 47% of superficial vs. 51% of muscle-invasive tumors (P D 0.815), were immunoreactive for ERb. In BCs, the positive rates of ERb expression ranged from 22 to 76%, 14,18,21,22,26,27 which was significantly lower than those in non-neoplastic bladder tissues.…”
Section: Discussionmentioning
confidence: 84%
“…Shyr et al 11 showed that 36 (43%) of 83 UUTUCs, including 44% of low-grade vs. 43% of high-grade tumors (P D 1.000) as well as 47% of superficial vs. 51% of muscle-invasive tumors (P D 0.815), were immunoreactive for ERb. In BCs, the positive rates of ERb expression ranged from 22 to 76%, 14,18,21,22,26,27 which was significantly lower than those in non-neoplastic bladder tissues.…”
Section: Discussionmentioning
confidence: 84%
“…Several studies have identified ER-b expression in a high proportion of bladder cancer cases. [11][12][13] In superficial bladder cancer, ER-b expression is 12% compared with 70% in MIBC. 17 In a study by Shen et al, 11 ER-b expression was detected in 63% of the bladder tumors (58% and 70% of World Health Organization grade 1/2 and grade 3 tumors, respectively; P ¼ .085).…”
Section: Discussionmentioning
confidence: 97%
“…[11][12][13] Increased ER-b and lower ER-a expression have been reported in high-grade bladder tumors and MIBC. [11][12][13][14][15][16] Moreover, increased ER-b expression was found to be associated with worse survival outcomes and increased risk of diseasespecific mortality when compared with tumors with decreased ER-b expression. However, these results are not consistent across different studies, and the discrepancies in part may be due to differences in study design, tissue collection, staining methods, and criteria for determining assay positivity.…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, a smaller study of 17 postmenopausal women indicated that the bladder transitional epithelium was negative for ERα, while transitional epithelium of the urethra was positive [21]. Expression of ERβ in the normal urothelium has also been evaluated in several studies, and the preponderance of results indicates that this tissue is largely positive for ERβ [20][21][22][23] with the exception of one report that indicated that approximately one-third of the female specimens was ERβ-positive, while this receptor was undetected in 58 male samples [8]. In rodents, there appears to be negligible ERα nuclear staining in the bladder [24,25], but ERβ is expressed in the urothelium and smooth muscle in both sexes [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 94%
“…A recent report indicated weak expression of ERα in 27% of primary bladder cancer tissues, with no correlation between ERα and tumor recurrence, progression, or cancer-specific survival [20]. In contrast, strong ERβ is detected in human bladder cancers in multiple studies, with up to 81% of tumors expressing this form of ER [8,9,20,22,35,39,40]. Expression of ERβ appears to be greater in high-grade versus low-grade tumors [20,35] and is associated with recurrence and progression of low-grade tumors, recurrence of muscle-invasive tumors, and reduced cancer-specific survival [20].…”
Section: Introductionmentioning
confidence: 99%